Comparative Effectiveness of Bariatric Surgery Versus GLP‐1 Receptor Agonists in Reducing the Risk of New‐Onset of NASH: A Retrospective Multinational Cohort Study From North America and Europe - Abdallah Hussein; Ameer Awashra; Islam Rajab; Mohammad Bdair; Dawoud Hamdan; Ahmad Nouri; Elaf Khatib; Ghiras Khatib; Nyan Latt (Endocrinology, Diabetes & Metabolism)
ABSTRACT Background Nonalcoholic steatohepatitis (NASH) is a severe form of nonalcoholic fatty liver disease (NAFLD) that can progress to cirrhosis and hepatocellular carcinoma (HCC). Obesity is a major risk factor for NASH, and metabolic interventions such as bariatric surgery (BS) and glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) have been explored for their impact on liver‐related outcomes. This study evaluates the comparative effectiveness of BS and GLP‐1 RAs in reducing the incidence of new‐onset NASH and related hepatic complications. Methods This was a large, population‐based, retrospective cohort using data from the TriNetX platform. Adult patients with a body mass index (BMI, of 35 or greater and without a history of NAFLD/NASH (without cirrhosis) who underwent BS versus GLP‐1RA between January 1, 2014 and December 31, 2019, were included. Patients in the BS group were matched with patients in the GLP‐1RA group according to age, demographics, comorbidities and medication by using 1:1 propensity matching. Results Among 180,022 eligible adults, 143,404 underwent BS, while 36,618 received GLP‐1 RA therapy. Following propensity score matching, 33,594 patients in the BS group (mean age 49.1 ± 13.2 years; 72.73% female) were matched to an equal number of individuals in the GLP‐1 RA group (mean age 48.9 ± 14.0 years; 72.41% female). Compared to those receiving GLP‐1 RA therapy, patients who underwent BS had a significantly lower risk of HCC (HR, 0.304; 95% CI, 0.099–0.931), which showed the strongest protective effect, followed by a substantial reduction in NASH (HR, 0.509; 95% CI, 0.469–0.551). The reduction in liver cirrhosis risk was not statistically significant (HR, 0.865; 95% CI, 0.696–1.075). These associations remained across follow‐up periods of 1, 3, 5 and 7 years. Conclusions These findings suggest that BS was significantly associated with lower risk of new onset of NASH/NAFLD.